Baicalin Alleviate Apoptosis via PKC-MAPK Pathway in Porcine Peritoneal Mesothelial Cells Induced by Glaesserella parasuis - Qirong Lu; Lang Zhou; Ziyue Wang; Xiaomin Li; Li Ding; Yinsheng Qiu; Pu Guo; Chun Ye; Shulin Fu; Zhongyuan Wu; Yu Liu (Molecules, 2022)
Glaesserella parasuis (GPS), a causative agent of Glässer’s disease, is thought to be the main fatal cause of peritonitis in swine, thus resulting in high mortality and morbidity and significant economic losses to the swine industry. However, the mechanisms of GPS infection-induced apoptosis and possible therapeutic pathway for GPS infection in peritonitis remain unclear. Baicalin has important biological functions during disease treatment, such as antiviral, bacterial inhibition, anti-apoptosis, and anti-inflammatory. However, whether baicalin has anti-apoptotic effects during the process of GPS infection in peritonitis is unclear. In the present study, the anti-apoptotic effect and mechanisms of baicalin in GPS infection-induced apoptosis were investigated in porcine peritoneal mesothelial cells (PPMC). The results showed that baicalin could inhibit the apoptosis rate occurrence of PPMC induced by GPS to various degrees and inhibit the expression of apoptosis-related genes and cleaved caspase-3. Meanwhile, baicalin significantly antagonized the expression of p-JNK, p-p38, and p-ERK induced by GPS in PPMC. These findings for the first time demonstrate that baicalin exerted the effect of antagonizing GPS induced apoptosis in PPMC by inhibiting the activation of the PKC-MAPK pathway and could be a therapeutic option in the management of GPS infection.